CO2-enhanced catalytic processing of oil shale - Tang, Luyao (2019)
Oil shale is a complex mixture consisting of organic matters, mineral matrix and small amount of bound and unbound water. The thermal decomposition of organic substance generates oil and gaseous products. Operating conditions significantly influence the product yield. N2 pyrolysis and CO2-enhanced pyrolysis of small batch of fine oil shale and oil shale/shale ash blends provided different characteristics in both reactions and pyrolyzed products. Co processing of oil shale and agricultural wastes were also investigated in this thesis. First of all, characterization of oil shale, shale ash and agricultural wastes were conducted in order to understand the nature of samples by multiple characterization techniques. Four types of oil shale and shale ash from various regions were used in this study. The kinetic study was carried out for both N2 pyrolysis and CO2-enhanced pyrolysis with four different mathematical models, including Kissinger method, FWO method, KAS method and Coats-Redfern method. Thermal decomposition properties of oil shale and agricultural wastes were studied based on TG and DTG curves results. Activation energy values produced by Coats-Redfern method were compared in pyrolysis reactions in different samples. Alkali index calculated from XRF results was used to identify different catalytic behaviors of shale II ash. In N2 pyrolysis process, gaseous products and shale oil were analyzed by gas chromatography and gas chromatography-mass spectrometry. Peak temperature was found an apparent decrease (10-30︒C) in oil shale/shale ash blends N2 pyrolysis tests compared with oil shale in N2 pyrolysis. Activation energy values of oil shale/shale ash blends also reduced significantly, by around 30 kJmol-1 compared with individual oil shale in N2 pyrolysis. Product yield and shale oil yield were enhanced up to 36% by shale ash catalytic effects. Syngas concentration was also increased up to 14.80% under this circumstance. In CO2-enhanced pyrolysis tests, oil shale with higher ash content showed lower reactivity in the reactions, especially in initial and final stages. Compared with N2 pyrolysis tests, CO2 enhanced pyrolysis tests results exhibited higher yield and selectivity in syngas, from 14.80% to 20.30%. Though shale oil yield was decreased, gas yield was apparently increased. The main purpose of utilizing agricultural wastes and oil shale in pyrolysis process is turning waste materials into high-added value products. In the co-pyrolysis process, different blending ratio had various effects on thermal decomposition process. Residual mass content increase with increasing oil shale content. This trend was due to the high volatile content and low fixed carbon content in agricultural wastes compared to oil shale. The agricultural wastes contained III cellulose, hemicellulose and lignin, which constituted the macromolecular structure of woody materials. The highest activation energy was observed in the final period of pyrolysis with blending ratio of 7:3 (agricultural wastes to oil shale). Activation energy was considered as initiative energy barrier in the reaction. This implied that lower activation energy could promote co-pyrolysis process. Shale ash can be used as potential catalysts in N2 pyrolysis and CO2 enhanced pyrolysis because of thermal stability and splendid behavior. Co-processing of oil shale and other organic-rich materials is an efficient approach for the conversion of oil shale into high-value products.